(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2021)
We present a new iterative technique based on successive field propagation using the Reyleigh-Sommerfeld (RS) approximation, to generate by computer the amplitude on-axis hologram of an object on a tilted plane. The technique was validated doing optical and computational reconstruction of the hologram.